Sample Size Estimation in Medical Research Based Upon Study Design - Upadhyay, Hari Prasad; Pradhan, Bijay Lal (Journal of College of Medical Sciences-Nepal, 2023)
Background: In medical research the target of researcher is to generalize the finding to the population based upon the information of sample data. This sample has to be representative of the target population, and the number of participants must be appropriate. The determination of minimum optimum sample size is extremely important not only for ethical and economic purposes but also to achieve scientifically and statistically sound results and valid conclusion. Conclusion: Choosing the best study design and calculation of sample size are the most important tool in any research. Before you plan any type of medical research either you should have good knowledge on research methodology or you should meet to professional statistician and ask for help at the time of planning a research project to avoid methodological errors.